(3EOGQI GdLhOI GdTGedI heJWdHGJ GdGjRh (B9001:2000s - (3bGSe fGja(B, (3YdhGfs ((3YeGf(B:s (3OGQ GdKbGaI ddfTQ(B,s, 2005)
(3jYJHQ GdcJGH eQLY LjOkG MjK jecf GdGSJaGOI efg agh jbOe eYdheGJ hGajI hYGeI dacQI hadSaI GdLhOI hGQOGI GdLhOI GdTGedI hSdSdI ehGUaGJ GdGjRh(B. (3EecGfjI GdGSJaGOI hGdJYde ef gPG GdcJGH ddeHJOFjf aj Yde GdLhOI LjOI LOkG , GPG cfJe ef GdQjGOjf h SJHODf eTQhYce GdNGU Ch cfJe SJYedhf aj TQcI Gh efXeI MUdJ Ydi GdGjRh Gh JYed LGgOI dPdc agPG GdcJGH dce (B.(3hdeQGLYI aUhd GdcJGH agj JJfGhd GdehGVjY GdJGdjI (B: (3GdaUd GdChd (B: (3GdJYQja HGdLhOI heQGMd JWhQgG GdaUd GdKGfj (B: (3fXGe VHW GdLhOI GdaUd GdKGdK (B: (3GdGWGQ GdacQj dGOGQI GdLhOI GdTGedI GdaUd GdQGHY (B:(3eJWdHGJ EOGQI GdLhOI GdTGedI heQGMd JWHjbgG GdaUd GdNGeS (B: (3OhQ MdbGJ GdLhOI aj JWhjQ EOGQI GdTGedI GdaUd GdSGOS (B: (3EOGQI GdLhOI GdTGedI (B:(3OQGSI MGdI JWHjbjI GdaUd GdSGHY (B: (3GdNdajI GdYGeI dSdSdI ehGUaGJ GdGjRh (BISO9000 (3GdaUd GdKGef (B:(3WHjYI GdehGUaGJ GdOhdjI GjRh(BISO9001:2000 (3GdaUd GdJGSY (B: (3GdehGUaI GdOhdjI GjRh (B:ISO 9001:2000 (3OQGSI MGdI JWHjbjIs
Keywords: (3GdEOGQIs; (3VHW GdLhOIs; (3efXeGJ GdJbjjS (B_ (3GjRhs